Protocol, rationale and design of BE-PEOPLE (Bedaquiline enhanced exposure prophylaxis for LEprosy in the Comoros): a cluster randomized trial on effectiveness of rifampicin and bedaquiline as post-exposure prophylaxis of leprosy contacts - Younoussa, Assoumani; Samidine, Said Nourdine; Bergeman, Auke T.; Piubello, Alberto; Attoumani, Nissad; Grillone, Silahi Halifa; Braet, Sofie Marijke; Tsoumanis, Achilleas; Baco, Abdallah; Mzembaba, Aboubacar; Salim, Zahara; Amidy, Mohamed; et al. (BMC infectious diseases, 2023)
Background Leprosy is an ancient infectious disease with an annual global incidence of around 200,000 over the past decade. Since 2018, the World Health Organization (WHO) recommends single-dose rifampicin as post-exposure prophylaxis (SDR-PEP) for contacts of leprosy patients. The Post ExpOsure Prophylaxis for Leprosy (PEOPLE) trial evaluated PEP with a double dose of rifampicin in Comoros and Madagascar. Preliminary results of this trial show some reduction in leprosy incidence in intervention villages but a stronger regimen may be beneficial. The objective of the current Bedaquiline Enhanced ExpOsure Prophylaxis for LEprosy trial (BE-PEOPLE) is to explore effectiveness of a combination of bedaquiline and rifampicin as PEP. Methods BE-PEOPLE is a cluster-randomized trial in which 44 clusters in Comoros will be randomized to two study arms. Door-to-door screening will be conducted annually during four years, leprosy patients identified will be offered standard of care treatment. Based on study arm, contacts aged five years and above and living within a 100-meter radius of an index case will either receive bedaquiline (400-800 mg) and rifampicin (150-600 mg) or only rifampicin (150–600 mg). Contacts aged two to four years will receive rifampicin only. Household contacts randomized to the bedaquiline plus rifampicin arm will receive a second dose four weeks later. Incidence rate ratios of leprosy comparing contacts who received either of the PEP regimens will be the primary outcome. We will monitor resistance to rifampicin and/or bedaquiline through molecular surveillance in all incident tuberculosis and leprosy patients nationwide. At the end of the study, we will assess anti- M. leprae PGL-I IgM seropositivity as a proxy for the population burden of M. leprae infection in 8 villages (17,000 individuals) that were surveyed earlier as part of the PEOPLE trial. Discussion The COLEP trial on PEP in Bangladesh documented a reduction of 57% in incidence of leprosy among contacts treated with SDR-PEP after two years, which led to the WHO recommendation of SDR-PEP. Preliminary results of the PEOPLE trial show a lesser reduction in incidence. The BE-PEOPLE trial will explore whether reinforcing SDR-PEP with bedaquiline increases effectiveness and more rapidly reduces the incidence of leprosy, compared to SDR-PEP alone. Trial registration NCT05597280. Protocol version 5.0 on 28 October 2022.